Insulated gate bipolar transistor (IGBT) : theory and design - Khanna, Vinod Kumar, 1952-; John Wiley & Sons; IEEE Xplore (Online service) (Piscataway, New Jersey : IEEE Press, 2003)
A comprehensive and "state-of-the-art" coverage of the design and fabrication of IGBT. . All-in-one resource. Explains the fundamentals of MOS and bipolar physics.. Covers IGBT operation, device and process design, power modules, and new IGBT structures.
Preface. -- Power Device Evolution and the Advert of IGBT. -- IGBT Fundamentals and Status Review. -- MOS Components of IGBT. -- Bipolar Components of IGBT. -- Physics and Modeling of IGBT. -- Latch-Up of Parasitic Thyristor in IGBT. -- Design Considerations of IGBT Unit Cell. -- IGBT Process Design and Fabrication Technology. -- Power IGBT Modules. -- Novel IGBT Design Concepts, Structural Innovations, and Emerging Technologies. -- IGBT Circuit Applications. -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web
Description based on PDF viewed 12/21/2015.
Keywords: Insulated gate bipolar transistors; Electrical and Electronics Engineering; Electronic books